Reducing energy consumption during bitumen separation from oil sand - Nikolay Bukharin; Mouhammad El Hassan; David Nobes; Maxim Omelyanyuk (Energy Reports, 2020)
Oil sands, found in Canada, Venezuela, USA and Russia, contain bitumen, water, clay and some metals. Two different methods of producing oil from oil sands exist: open-pit mining and in situ. Approximately 20% of oil sands are recoverable through open-pit mining. After oil sand is mined, bitumen is separated from solids and water within the bitumen production facilities. The process of bitumen separation consists of 3 main steps. (1) Hot/warm water is added to the oil sands producing a slurry that can be pumped to the processing plant through hydrotransport pipelines which connect ore preparation to the main extraction facility. These large-diameter pipelines can be several kilometers long, providing the additional time and shear required to break down the lumps of mined oil sands. (2) After hydrotransport pipeline oil sand slurry enters flotation facility where bitumen is gravity separated from the coarse solids producing an intermediate bitumen froth product. (3) Then solvent is added to the froth, to reduce the bitumen viscosity and to remove remaining water and fine solids. In addition to efficiency concerns, this separation process suffers from high operating cost due to a number of factors such as the energy needed for heating the water, the energy consumed by the cyclofeeder and the energy consumed by hydrotransport. The other problem of hydrotransport is extensive wear since the slurry contains quartz sand particles which are extremely abrasive. In the present study, an alternative technology based on cavitation jets is suggested. It is found that jets can separate bitumen at low temperatures (5-6~°C) and cavitation jet technologies have the potential to replace hydrotransport. A series of nozzles were designed for low intensity cavitation at high cavitation numbers (σ=0.37 - 0.46) to test different types of cavitation generators. It was shown that selfresonating nozzle shows significantly better results than conventional nozzles and conventional nozzles with passive control.
Keywords: 330; Bitumen separation; Cavitation; Cavitation jet; Energy; Hydrodynamic jet; Jets; Sustainability